Pelatihan Pembuatan Pupuk Kompos dari Limbah Rumah Tangga bagi Masyarakat di Desa Tritiro Kec. Bontotiro Kab. Bulukumba - GH, Muliana; Arsal, Andi Farida; Lismayani, Angri; Sadriani, Andi; Ruslan, Zuhrah Adminira (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
Household waste is daily waste generated by every household. Housel hold waste generated can be in the form of organic waste or inorganic waste. Which are difficult to decompose in the environment, such as plastic and cans. Oen way to utilize and process organic waste is through the manufacture of compost using a simple composter. This socialization activity and training on composting was carried out in Tritiro village, Bulukumba. The community service partners are housewives who live in Tritiro Village, Samboang District, Bulukuma Regency. This activity begins with counseling and outreach activities regarding compost, then training on the process of making compost from household waste. Key word : household waste, composter, compost manure